2013
DOI: 10.1021/ic401270j
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Atom Transfer from Iodosylarene Adducts of a Manganese(IV) Salen Complex: Effect of Arenes and Anions on I(III) of the Coordinated Iodosylarene

Abstract: This paper reports preparation, characterization, and reactivity of iodosylarene adducts of a manganese(IV) salen complex. In order to systematically investigate steric and electronic factors that control reactivity and selectivity, we prepared iodosylarene adducts from iodosylbenzene, iodosylmesitylene, 2,4,6-triethyliodosylbenzene, and pentafluoroiodosylbenzene. We also investigated the effect of anions on I(III) by using chloride, benzoate, and p-toluenesulfonate. Spectroscopic studies using (1)H NMR, elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…23 The effects of axial donors on nonheme Mn(O) complexes such as Mn(O)(salen)(X) have been reported. 3134 However, direct structural, spectroscopic, or reactivity information on these complexes is in general quite limited because of the transient nature of these species. 31 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The effects of axial donors on nonheme Mn(O) complexes such as Mn(O)(salen)(X) have been reported. 3134 However, direct structural, spectroscopic, or reactivity information on these complexes is in general quite limited because of the transient nature of these species. 31 …”
Section: Introductionmentioning
confidence: 99%
“…3134 However, direct structural, spectroscopic, or reactivity information on these complexes is in general quite limited because of the transient nature of these species. 31 …”
Section: Introductionmentioning
confidence: 99%
“…For example, Fujii and co-workers reported that iron(III)-OCl porphyrin and manganese(IV) iodosylarene salen complexes are competent oxidants in OAT reactions. [5] McKenzie and Lennartson reported a crystal structure of a nonheme iron(III) iodosylbenzene complex and used it in a sulfoxidation reaction. [6] Lei and coworkers reported spectroscopic evidence for a manganese iodosylarene porphyrin adduct.…”
mentioning
confidence: 99%
“…The reactivities of the iron(III)-iodosylarene adducts, 2 and 3, were investigated in the CÀH bond activation of hydrocarbons at À40 8C. Upon addition of cumene to a solution of 2, the intermediate was converted into a new species (5) which gives rise to an isosbestic point at l = 537 nm (Figure 2 a). First-order rate constants, determined by the pseudo-first-order fitting of the kinetic data for the decay of 2 (Figure 2 a, inset), increased linearly with increasing cumene concentration, giving rise to a second-order rate constant of 2.1 10 À1 m À1 s À1 at À40 8C.…”
mentioning
confidence: 99%
“…Metal-salen complexes are known to be powerful and robust catalysts and their planar structures make them an ideal choice to mimic the structure of porphyrins so that the active sites of the hemoproteins stay relatively unchanged [61][62][63][64][65]. Figure 6 shows the comparison of protoporphyrin IX and two salen metal complexes that have been utilized as surrogates for the heme cofactor.…”
Section: Insertion Of Schiff-base Cofactors Into Myoglobinmentioning
confidence: 99%